Rubber composition and rubber material preparation method

Through precise proportion and process step optimization, the strength, damping characteristics and aging resistance of rubber materials are improved, and the problems of insufficient performance of traditional rubber compositions and nanofiller agglomeration are solved, thereby realizing the preparation of high-performance rubber materials.

CN119613838APending Publication Date: 2025-03-14QINGDAO GLOBAL CONVEYOR BELT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411938236.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional rubber compositions have shortcomings in strength, damping characteristics, aging resistance and adhesive properties, and excessive use of nanofillers can easily lead to agglomeration and a decrease in the number of reinforcement.

Method used

By accurately proportioning rubber matrix, methacrylic acid, cationic surfactant modified montmorillonite, vulcanizing agent, anti-aging agent and reinforcement, the performance of rubber materials is significantly improved.

Benefits of technology

It significantly improves the strength, damping characteristics and aging resistance of rubber materials, reduces the agglomeration phenomenon of nanofillers, ensures the uniform distribution of reinforcement, and improves the overall performance and production efficiency of rubber materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613838A_ABST
    Figure CN119613838A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of rubber preparation, and discloses a rubber composition and a rubber material preparation method, the rubber composition comprises a rubber composition, and the rubber composition is formed by the following components: a rubber matrix; methacrylic acid; montmorillonite modified by a cationic surface active agent; a vulcanizing agent; an anti-aging agent and a reinforcing agent; in order to prepare the rubber composition, the invention provides a rubber material preparation method which comprises the following steps: step S1, raw material pretreatment; step S2, banburying and mixing; s3, adding a reinforcing agent; step S4, extruding and granulating; step S5, vulcanization molding; and step S6, performing post-treatment. According to the invention, the strength, the damping characteristic and the aging resistance of the rubber material are obviously improved; a double-bond binding site provided by methacrylic acid is combined with the electrostatic interface action of the modified montmorillonite, so that the interaction between rubber molecules and the nano filler is effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber preparation, in particular to a rubber composition and a method for preparing a rubber material. Background Art

[0002] Rubber compositions and their preparation methods have a wide range of applications in many fields, including but not limited to automobile tires, seals, vibration damping materials, etc. With the advancement of science and technology and changes in market demand, the performance requirements for rubber compositions are also increasing. Although traditional rubber compositions have good performance in some aspects, they still need to be improved in terms of strength, damping properties, aging resistance and bonding properties.

[0003] After searching, the Chinese patent number CN107641176B discloses a rubber composition and a method for preparing a rubber material, which belongs to the field of rubber. The rubber composition includes rubber, methacrylic acid, montmorillonite modified by a cationic surfactant, a vulcanizing agent and an antioxidant. The rubber composition improves the internal stress transmission capacity of the rubber through interactions such as electrostatic interface, double bond bonding or physical entanglement, so as to achieve the purpose of further improving the performance of the rubber by using a small amount of nanofiller, avoiding the problem that the performance of the rubber does not meet the use requirements when the amount of nanofiller is small, and the problem that the amount of nanofiller is too large to easily lead to agglomeration, thereby causing the reinforcement force to decrease.

[0004] After searching, the Chinese patent number CN114292454B discloses a rubber composition and a method for preparing a rubber material, which belongs to the field of rubber. The rubber composition includes rubber, methacrylic acid, montmorillonite modified by a cationic surfactant, a vulcanizing agent and an antioxidant. The rubber composition improves the internal stress transmission capacity of the rubber through interactions such as electrostatic interface, double bond bonding or physical entanglement, so as to achieve the purpose of further improving the performance of the rubber by using a small amount of nanofiller, avoiding the problem that the performance of the rubber does not meet the use requirements when the amount of nanofiller is small, and the problem that the amount of nanofiller is easy to cause agglomeration, thereby causing the reinforcement force to decrease.

[0005] The above patents all claim that the internal stress transfer capacity of rubber is improved through interactions such as electrostatic interface, double bond bonding or physical entanglement, thereby achieving the purpose of improving rubber performance by using a small amount of nanofiller, but do not specify the specific aspects of the improvement, and whether the deficiencies of traditional rubber compositions in strength, damping characteristics and aging resistance have been fully solved; secondly, the above patents all mention that excessive use of nanofillers can easily lead to agglomeration, thereby causing a decrease in the reinforcement number, but do not provide detailed solutions to solve the problem. Based on this, the present invention designs a rubber composition and a method for preparing a rubber material to solve the above problems. Summary of the invention

[0006] The object of the present invention is to provide a rubber composition and a method for preparing a rubber material, which solves the problem that the specific aspects of the improvement are not specifically described in the background technology and the detailed solution is not provided.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A rubber composition and a method for preparing a rubber material, comprising a rubber composition, wherein the rubber composition is formed by the following components:

[0009] Rubber matrix: 78%-88%, used to form the main body of the composition;

[0010] Methacrylic acid: 3%-6%, used to provide double bond binding sites and enhance the interaction between rubber and nanofiller;

[0011] Cationic surfactant-modified montmorillonite: 1%-3%, which improves the internal stress transmission capacity of rubber through electrostatic interface effect. The interlayer spacing of the modified montmorillonite is increased by 20% to optimize its dispersibility in the rubber matrix;

[0012] Vulcanizing agent: 0.6%-2.5%, used for cross-linking and curing of rubber;

[0013] Antiaging agent: 1%-3%, used to improve the aging resistance of rubber;

[0014] and reinforcing agents: 0.2%-1.5%, such as carbon fiber or nano-silica, to enhance specific properties of the rubber, including strength and damping characteristics;

[0015] To prepare a rubber composition, a method for preparing a rubber material is provided, comprising the following steps:

[0016] Step S1, raw material pretreatment: drying the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent, antioxidant and reinforcing agent respectively;

[0017] Step S2, internal mixing: using an internal mixer, preliminarily mixing the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent and antioxidant;

[0018] Step S3, adding reinforcing agent: continue to add reinforcing agent in the internal mixer to make the reinforcing agent evenly dispersed in the rubber matrix;

[0019] Step S4, extrusion granulation: extruding and granulating the uniformly mixed rubber material through a twin-screw extruder;

[0020] Step S5, vulcanization molding: placing the cooled rubber particles in a flat vulcanizer for vulcanization;

[0021] Step S6, post-processing: the vulcanized rubber material is trimmed and inspected.

[0022] Preferably, the rubber matrix is ​​a mixture of one or more of natural rubber, styrene-butadiene rubber, butadiene rubber or ethylene-propylene rubber.

[0023] Preferably, the cationic surfactant-modified montmorillonite is prepared by the following steps:

[0024] Step a, mixing the original montmorillonite and the cationic surfactant in a mass ratio of 1:0.5-1:2;

[0025] Step b, stirring and reacting at 80-100° C. for 2-4 hours;

[0026] Step c: washing and drying to obtain modified montmorillonite.

[0027] Preferably, in the step S1, during the drying process, it is necessary to ensure that the water content does not exceed 0.5% to avoid generating bubbles or affecting the rubber properties during subsequent processing; in the step S2, the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent and antioxidant are preliminarily mixed at a temperature of 130°C-150°C, the mixing time is 8-12 minutes, and the rotation speed is controlled at 50-70rpm to ensure that the components are fully dispersed and evenly mixed.

[0028] Preferably, in step S3, the reinforcing agent includes a mixture of carbon fiber and nano-silicon dioxide in a ratio of 1:1, and the mixture is mixed for 2-4 minutes to uniformly disperse the reinforcing agent in the rubber matrix, and the double bond binding sites provided by methacrylic acid are utilized to enhance the interaction between the rubber and the reinforcing agent; in step S4, the extrusion temperature is controlled at 160°C-180°C, and the screw speed is 20-40rpm to ensure the uniformity and quality of the extrudate, and the rubber particles after extrusion are cooled to avoid thermal deformation.

[0029] Preferably, in step S5, vulcanization is performed at a temperature of 150°C-170°C and a pressure of 10-20 MPa, and the vulcanization time is 15-25 minutes; in step S6, the vulcanized rubber material is trimmed and inspected to remove burrs and unqualified parts to ensure that the product meets quality standards.

[0030] Preferably, in step S2, the vulcanizing agent is a mixture of one or more of sulfur, dibenzoyl peroxide or diisopropylbenzene peroxide; the antioxidant is a mixture of one or more of hindered phenols, amines or thioester antioxidants, which are used to improve the oxidation resistance, ozone resistance and UV resistance of the rubber.

[0031] Preferably, in step S3, the reinforcing agent is chopped carbon fiber or nano-silicon dioxide, wherein the length of the chopped carbon fiber is 3-10 mm and the diameter is 5-20 μm; the particle size of the nano-silicon dioxide is 10-50 nm, so as to further improve the strength and damping properties of the rubber.

[0032] Preferably, during the preparation process of the rubber material, a dynamic viscosity test is performed using a rheometer to monitor the fluidity and processing performance of the rubber material to ensure the stability and controllability of the preparation process.

[0033] Preferably, after vulcanization, the rubber material is tested for tensile strength and elongation at break using a universal material testing machine to ensure that the mechanical properties of the rubber material meet the design requirements according to the ASTM D412 standard; after vulcanization, the rubber material is tested for damping performance using a dynamic mechanical analyzer to evaluate the damping coefficient and loss factor of the rubber material within a specific frequency range according to the ISO 6393 standard to ensure that the damping characteristics of the rubber material meet the application requirements.

[0034] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0035] 1. The present invention significantly improves the strength, damping characteristics and aging resistance of rubber materials by accurately mixing rubber matrix, methacrylic acid, montmorillonite modified by cationic surfactant, vulcanizing agent, antioxidant and reinforcing agent; the double bond binding sites provided by methacrylic acid are combined with the electrostatic interface effect of modified montmorillonite to effectively enhance the interaction between rubber molecules and nanofillers, so that even when the amount of nanofillers is small, the rubber performance can be significantly improved, providing a new way to improve the high performance of rubber materials.

[0036] 2. In order to solve the problem that excessive use of nanofillers easily leads to agglomeration, thereby reducing the reinforcement number, the present invention adopts montmorillonite modified by a cationic surfactant and significantly increases the interlayer spacing of montmorillonite through a specific preparation process, thereby optimizing its dispersibility in the rubber matrix. This innovative method effectively reduces the agglomeration of nanofillers and ensures the uniform distribution of the reinforcing agent in the rubber matrix, thereby improving the overall performance of the rubber material.

[0037] 3. The present invention introduces advanced equipment such as a rheometer, a universal material testing machine and a dynamic mechanical analyzer during the preparation process of the rubber material to monitor and test the fluidity, mechanical properties and damping properties of the rubber material in real time. Through this method, the present invention effectively solves the problems of uneven mixing and extrusion difficulties that may occur in the processing of traditional rubber compositions, thereby improving the production efficiency and product quality of rubber materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a composition diagram of the rubber composition of the present invention;

[0039] Figure 2 is a flow chart of the method for preparing the rubber material of the present invention;

[0040] Figure 3 The present invention is a flow chart of the preparation of the cationic surfactant-modified montmorillonite;

[0041] Figure 4 This is a diagram showing the effect improvement of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Embodiment 1;

[0044] See also Figure 1-Figure 4 In an embodiment of the present invention, a rubber composition and a method for preparing a rubber material are characterized in that they include a rubber composition, wherein the rubber composition is formed by the following composition:

[0045] Rubber matrix: 78%-88%, used to form the main body of the composition;

[0046] Methacrylic acid: 3%-6%, used to provide double bond binding sites and enhance the interaction between rubber and nanofiller;

[0047] Cationic surfactant-modified montmorillonite: 1%-3%, which improves the internal stress transmission capacity of rubber through electrostatic interface effect. The interlayer spacing of the modified montmorillonite is increased by 20% to optimize its dispersibility in the rubber matrix;

[0048] Vulcanizing agent: 0.6%-2.5%, used for cross-linking and curing of rubber;

[0049] Antiaging agent: 1%-3%, used to improve the aging resistance of rubber;

[0050] and reinforcing agents: 0.2%-1.5%, such as carbon fiber or nano-silica, to enhance specific properties of the rubber, including strength and damping characteristics;

[0051] To prepare a rubber composition, a method for preparing a rubber material is provided, comprising the following steps:

[0052] Step S1, raw material pretreatment: drying the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent, antioxidant and reinforcing agent respectively;

[0053] Step S2, internal mixing: using an internal mixer, preliminarily mixing the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent and antioxidant;

[0054] Step S3, adding reinforcing agent: continue to add reinforcing agent in the internal mixer to make the reinforcing agent evenly dispersed in the rubber matrix;

[0055] Step S4, extrusion granulation: extruding and granulating the uniformly mixed rubber material through a twin-screw extruder;

[0056] Step S5, vulcanization molding: placing the cooled rubber particles in a flat vulcanizer for vulcanization;

[0057] Step S6, post-processing: the vulcanized rubber material is trimmed and inspected.

[0058] The rubber matrix is ​​a mixture of one or more of natural rubber, styrene-butadiene rubber, butadiene rubber or ethylene-propylene rubber.

[0059] The cationic surfactant-modified montmorillonite is prepared by the following steps:

[0060] Step a, mixing the original montmorillonite and the cationic surfactant in a mass ratio of 1:0.5-1:2;

[0061] Step b, stirring and reacting at 80-100° C. for 2-4 hours;

[0062] Step c: washing and drying to obtain modified montmorillonite.

[0063] The working principle of the embodiment of the present invention is that each component of the rubber composition performs its own function in the formula design, and together constructs a rubber material with excellent performance. The rubber matrix, as the main component, provides the basic physical and chemical properties of the material and is the basis of the rubber material. The addition of methacrylic acid, through its double bond structure, provides more binding sites between the rubber molecules and the nanofiller, and this chemical bonding significantly enhances the interaction between the rubber and the filler.

[0064] Montmorillonite modified by cationic surfactant is a highly efficient nanofiller. Its modification process increases the interlayer spacing, optimizes the dispersion of fillers in the rubber matrix, and reduces agglomeration. The modified montmorillonite interacts with rubber molecules through electrostatic interface action, effectively improving the stress transfer capacity inside the rubber, so that the rubber material can distribute stress more evenly when subjected to force.

[0065] Vulcanizing agent plays a vital role in the cross-linking and curing process of rubber. It can promote the formation of chemical bonds between rubber molecular chains under certain temperature and pressure to form a three-dimensional network structure, thereby giving the rubber material good elasticity, strength and wear resistance. Antioxidants are added to improve the aging resistance of rubber and prevent it from degradation and aging due to factors such as light, heat and oxygen during long-term use.

[0066] The addition of reinforcing agents is to further enhance the specific properties of rubber, such as strength and damping characteristics. Reinforcing agents such as carbon fiber or nano-silica have excellent mechanical properties and chemical stability. They can be evenly dispersed in the rubber matrix to form an effective reinforcement system.

[0067] In terms of preparation methods, the uniform dispersion and effective combination of each component in the rubber matrix are ensured through the steps of raw material pretreatment, banburying and mixing, adding reinforcing agents, extrusion granulation, vulcanization molding and post-treatment. In particular, the banburying and mixing and extrusion granulation processes, through the action of mechanical force, make the components more closely combined to form a uniform rubber material. The vulcanization molding process makes the rubber material form a stable three-dimensional network structure, giving it good physical and chemical properties.

[0068] Embodiment 2;

[0069] See also Figure 1-Figure 4 In the embodiment of the present invention, in step S1, during the drying process, it is necessary to ensure that the water content does not exceed 0.5% to avoid generating bubbles or affecting the rubber properties during the subsequent processing; in step S2, the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent and antioxidant are preliminarily mixed at a temperature of 130°C-150°C, the mixing time is 8-12 minutes, and the rotation speed is controlled at 50-70rpm to ensure that the components are fully dispersed and evenly mixed.

[0070] In step S3, the reinforcing agent includes a mixture of carbon fiber and nano-silicon dioxide in a ratio of 1:1, and the mixture is mixed for 2-4 minutes to uniformly disperse the reinforcing agent in the rubber matrix, and at the same time, the double bond binding sites provided by methacrylic acid are used to enhance the interaction between the rubber and the reinforcing agent; in step S4, the extrusion temperature is controlled at 160°C-180°C, and the screw speed is 20-40rpm to ensure the uniformity and quality of the extrudate, and the rubber particles after extrusion are cooled to avoid thermal deformation.

[0071] In step S5, vulcanization is performed at a temperature of 150°C-170°C and a pressure of 10-20 MPa for 15-25 minutes; in step S6, the vulcanized rubber material is trimmed and inspected to remove burrs and unqualified parts to ensure that the product meets quality standards.

[0072] In step S2, the vulcanizing agent is a mixture of one or more of sulfur, dibenzoyl peroxide or diisopropylbenzene peroxide; the antioxidant is a mixture of one or more of hindered phenols, amines or thioester antioxidants, which are used to improve the oxidation resistance, ozone resistance and UV resistance of the rubber.

[0073] In step S3, the reinforcing agent is chopped carbon fiber or nano-silicon dioxide, wherein the length of the chopped carbon fiber is 3-10 mm and the diameter is 5-20 μm; the particle size of the nano-silicon dioxide is 10-50 nm, so as to further improve the strength and damping properties of the rubber.

[0074] The working principle of the embodiment of the present invention is: in the drying process of step S1, it is very important to strictly control the water content of the raw materials to below 0.5%. Too high water content may not only cause bubbles in subsequent processing, affect the density and appearance of the rubber, but also weaken the bonding force between rubber molecules, reduce its mechanical properties and durability.

[0075] Entering step S2, the preliminary mixing stage, precise control of temperature and time is crucial to achieve uniform dispersion of each component. In the temperature range of 130℃-150℃, the rubber matrix begins to soften, which is conducive to the penetration and mixing of other components. The mixing time of 8-12 minutes and the speed setting of 50-70rpm ensure that the components are fully and evenly mixed in the internal mixer, avoiding the occurrence of local uneven concentration or agglomeration.

[0076] In step S3, the addition and dispersion of the reinforcing agent is the key to improving the strength and damping properties of the rubber. Carbon fiber and nano-silica are mixed in a 1:1 ratio, using their respective advantages - the high strength of carbon fiber and the high specific surface area and excellent interface bonding ability of nano-silica - to jointly enhance the performance of the rubber. The mixing time of 2-4 minutes ensures the uniform distribution of the reinforcing agent in the rubber matrix. At the same time, the double bond binding sites provided by methacrylic acid promote the chemical bonding between the rubber molecules and the reinforcing agent, further enhancing the mechanical properties and durability of the rubber.

[0077] During the extrusion granulation process of step S4, precise control of the extrusion temperature and screw speed is crucial to ensure the quality and uniformity of the extrudate. The extrusion temperature of 160°C-180°C ensures the fluidity of the rubber material, while the screw speed of 20-40rpm contributes to the continuity and stability of the extrudate. The cooling treatment after extrusion avoids thermal deformation of the rubber particles due to residual heat, ensuring the smooth progress of subsequent vulcanization molding.

[0078] The vulcanization molding in step S5 is a key step in the preparation of rubber materials. Under a temperature of 150-170°C and a pressure of 10-20MPa, the vulcanizing agent promotes the formation of chemical bonds between rubber molecular chains to form a stable three-dimensional network structure. The vulcanization time of 15-25 minutes ensures that the rubber material achieves the best crosslinking density and physical properties. The vulcanized rubber material has excellent elasticity, strength and wear resistance.

[0079] Finally, in step S6, the vulcanized rubber material is trimmed and inspected to ensure that the product meets the quality standards. This step not only removes burrs and unqualified parts on the surface of the product, but also ensures the reliability and consistency of the product through strict inspection procedures.

[0080] Embodiment 3;

[0081] See also Figure 1-Figure 4 In the embodiment of the present invention, during the preparation process of the rubber material, a dynamic viscosity test is performed using a rheometer to monitor the fluidity and processing performance of the rubber material to ensure the stability and controllability of the preparation process.

[0082] After vulcanization, the rubber material is tested for tensile strength and elongation at break using a universal material testing machine to ensure that the mechanical properties of the rubber material meet the design requirements according to the ASTM D412 standard. After vulcanization, the rubber material is tested for damping performance using a dynamic mechanical analyzer to evaluate the damping coefficient and loss factor of the rubber material within a specific frequency range according to the ISO 6393 standard to ensure that the damping characteristics of the rubber material meet the application requirements.

[0083] The working principle of the embodiment of the present invention is as follows: the rheometer plays a vital role in the preparation stage of the rubber material. It applies shear force to the rubber material and measures the resulting stress change to calculate the dynamic viscosity of the material. Dynamic viscosity is an important indicator reflecting the fluidity of the material, which is directly related to the flow behavior and processability of the rubber material during processing. Through real-time monitoring of the rheometer, the flow properties of the rubber material can be accurately controlled to ensure that it maintains a stable flow state during processing such as mixing and extrusion, avoiding processing problems caused by insufficient or excessive fluidity, such as uneven mixing and difficult extrusion.

[0084] After the rubber material is vulcanized, the universal material testing machine becomes a key tool for evaluating its mechanical properties. It tests the tensile strength and elongation at break of the rubber material according to the ASTM D412 standard. The tensile strength refers to the maximum stress that the rubber material can withstand when subjected to a tensile force, while the elongation at break reflects the increase in the length of the material during the process of stretching to breaking.

[0085] The dynamic mechanical analyzer plays a key role in the damping performance test of rubber materials. It evaluates the damping coefficient and loss factor of vulcanized rubber materials within a specific frequency range in accordance with ISO 6393. The damping coefficient reflects the ability of the material to absorb and dissipate energy during vibration, while the loss factor characterizes the proportion of energy loss during vibration.

[0086] Working principle: During the preparation process, the raw materials are first pretreated to ensure the dryness of each component to avoid the adverse effects of moisture on the rubber properties; then, preliminary mixing is carried out in an internal mixer, and the temperature, time and speed are precisely controlled to achieve full dispersion and uniform mixing of the components; then, the reinforcing agent is added and mixing continues, and the double bond binding sites provided by methacrylic acid are used to enhance the interaction between the rubber and the reinforcing agent, further improving the strength and damping properties of the rubber; in the extrusion granulation stage, the uniformity and quality of the extrudate are ensured by precisely controlling the extrusion temperature and screw speed; in the vulcanization forming stage, under a certain temperature and pressure, the vulcanizing agent promotes the formation of chemical bonds between the rubber molecular chains to form a stable three-dimensional network structure, giving the rubber material good elasticity, strength and wear resistance; finally, through the post-processing steps, the vulcanized rubber material is trimmed and inspected to ensure that the product meets the quality standards.

[0087] In terms of performance improvement, the present invention significantly enhances the interaction between rubber and nanofiller by adding methacrylic acid and modified montmorillonite, and improves the stress transmission capacity inside the rubber. At the same time, the addition of the reinforcing agent further improves the strength and damping properties of the rubber. In addition, through the testing of advanced equipment such as rheometers, universal material testing machines and dynamic mechanical analyzers, it is ensured that the stability and controllability of the rubber material during the preparation process, as well as the mechanical properties and damping properties after vulcanization meet the design requirements.

[0088] Compared with the prior art, the present invention not only significantly improves the comprehensive performance of the rubber material, but also solves the problems of uneven mixing and extrusion difficulties that may occur during the processing. By comparing the performance improvement of the rubber composition and the problem solving (such as Figure 4 ), it can be seen that the present invention has significantly improved key performance indicators such as tensile strength, elongation at break, damping coefficient and loss factor, and effectively solved the problems of processing performance and aging resistance, providing a more reliable and efficient solution for the preparation and application of rubber materials.

[0089] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit thereof, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A rubber composition and a method for preparing a rubber material, characterized in that: The invention comprises a rubber composition, wherein the rubber composition is formed by the following composition: Rubber matrix: 78%-88%, used to form the main body of the composition; Methacrylic acid: 3%-6%, used to provide double bond binding sites and enhance the interaction between rubber and nanofiller; Cationic surfactant-modified montmorillonite: 1%-3%, which improves the internal stress transmission capacity of rubber through electrostatic interface effect. The interlayer spacing of the modified montmorillonite is increased by 20% to optimize its dispersibility in the rubber matrix; Vulcanizing agent: 0.6%-2.5%, used for cross-linking and curing of rubber; Antiaging agent: 1%-3%, used to improve the aging resistance of rubber; and reinforcing agents: 0.2%-1.5%, used to enhance specific properties of rubber, including strength and damping characteristics; To prepare a rubber composition, a method for preparing a rubber material is provided, comprising the following steps: Step S1, raw material pretreatment: drying the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent, antioxidant and reinforcing agent respectively; Step S2, internal mixing: using an internal mixer, preliminarily mixing the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent and antioxidant; Step S3, adding reinforcing agent: continue to add reinforcing agent in the internal mixer to make the reinforcing agent evenly dispersed in the rubber matrix; Step S4, extrusion granulation: extruding and granulating the uniformly mixed rubber material through a twin-screw extruder; Step S5, vulcanization molding: placing the cooled rubber particles in a flat vulcanizer for vulcanization; Step S6, post-processing: the vulcanized rubber material is trimmed and inspected.

2. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: The rubber matrix is ​​a mixture of one or more of natural rubber, styrene-butadiene rubber, butadiene rubber or ethylene-propylene rubber.

3. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: The cationic surfactant-modified montmorillonite is prepared by the following steps: Step a, mixing the original montmorillonite and the cationic surfactant in a mass ratio of 1:0.5-1:2; Step b, stirring and reacting at 80-100° C. for 2-4 hours; Step c: washing and drying to obtain modified montmorillonite.

4. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: In the step S1, during the drying process, it is necessary to ensure that the water content does not exceed 0.5% to avoid generating bubbles or affecting the rubber properties during the subsequent processing; in the step S2, the rubber matrix, methacrylic acid, modified montmorillonite, vulcanizing agent and antioxidant are preliminarily mixed at a temperature of 130°C-150°C, the mixing time is 8-12 minutes, and the rotation speed is controlled at 50-70rpm to ensure that the components are fully dispersed and evenly mixed.

5. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: In the step S3, the reinforcing agent includes a mixture of carbon fiber and nano-silicon dioxide in a ratio of 1:1, and the mixture is mixed for 2-4 minutes to uniformly disperse the reinforcing agent in the rubber matrix, and the double bond binding sites provided by methacrylic acid are used to enhance the interaction between the rubber and the reinforcing agent; in the step S4, the extrusion temperature is controlled at 160°C-180°C, and the screw speed is 20-40rpm to ensure the uniformity and quality of the extrudate, and the rubber particles after extrusion are cooled to avoid thermal deformation.

6. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: In the step S5, vulcanization is performed at a temperature of 150° C. to 170° C. and a pressure of 10-20 MPa for 15-25 minutes. In the step S6, the vulcanized rubber material is trimmed and inspected to remove burrs and unqualified parts to ensure that the product meets quality standards.

7. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: In step S2, the vulcanizing agent is a mixture of one or more of sulfur, dibenzoyl peroxide or diisopropylbenzene peroxide; the antioxidant is a mixture of one or more of hindered phenols, amines or thioester antioxidants, which are used to improve the oxidation resistance, ozone resistance and UV resistance of the rubber.

8. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: In step S3, the reinforcing agent is chopped carbon fiber or nano-silicon dioxide, wherein the length of the chopped carbon fiber is 3-10 mm and the diameter is 5-20 μm; the particle size of the nano-silicon dioxide is 10-50 nm, so as to further improve the strength and damping properties of the rubber.

9. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: During the preparation process of the rubber material, a dynamic viscosity test is performed using a rheometer to monitor the fluidity and processing performance of the rubber material to ensure the stability and controllability of the preparation process.

10. A rubber composition and a method for preparing a rubber material according to claim 1, characterized in that: After vulcanization, the rubber material is tested for tensile strength and elongation at break using a universal material testing machine to ensure that the mechanical properties of the rubber material meet the design requirements according to the ASTM D412 standard; after vulcanization, the rubber material is tested for damping performance using a dynamic mechanical analyzer to evaluate the damping coefficient and loss factor of the rubber material within a specific frequency range according to the ISO 6393 standard to ensure that the damping characteristics of the rubber material meet the application requirements.

Citation Information

Patent Citations

  • A rubber composition and a method for preparing rubber materials

    CN107641176B

  • A raw material composition for rubber paving material, the rubber paving material and its preparation method

    CN114292454B